Preparation and use method of biogas residue soft soil curing agent
By preparing the soft soil curing agent of slag, using porous biochar and composite exciter, combined with blast furnace slag and other materials, the existing soft soil curing methods are solved, and the efficient and economical soft soil curing effect is achieved.
Patent Information
- Application Number
- CN202411709141.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-21
AI Technical Summary
The existing soft soil curing methods are costly and difficult to completely fill the pores of the soil, and have poor resistance to seawater erosion.
The preparation and use method of slag soft soil curing agent is adopted to prepare porous biochar and composite exciter through solid-liquid separation, drying, alkali leaching, acid leaching, pyrolysis and other steps. Combined with blast furnace slag, fly ash and other materials, a slag soft soil curing agent with ultrafine pore structure and strong adsorption effect is formed.
It realizes efficient solidification of soft soil, reduces costs, improves the soil's resistance to seawater erosion and curing strength, and utilizes slag resources to achieve efficient utilization of resources.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0002] The present invention relates to a method for consolidating soft soil. Background Art
[0003] Coastal soft soil has the characteristics of high water content and large porosity. At the same time, it is corroded by the dry-wet cycle of seawater. How to efficiently solidify this kind of high-porosity and easily corroded soft soil in engineering is a difficult problem. The current solidification methods of coastal soft soil are: first, use a large amount of cement to harden the soft soil to meet engineering requirements; second, use a mixture of cement, slag, fly ash and other industrial waste to solidify the soft soil to reduce cement consumption and reduce costs. However, it is difficult to completely fill the pores of the soil body with cementitious materials that rely solely on the hydration of cementitious cement, and cement-based materials have poor resistance to seawater erosion. Third, alkali-activated geopolymer concrete is formed by using solid wastes such as slag, fly ash, and silica fume as raw materials and activating and solidifying them with alkaline activators. For example, Chinese patent application number 202310037457.9 discloses an alkali-activated geopolymer material, which includes amorphous aluminosilicate and an alkali activator, wherein the amorphous aluminosilicate includes SiO2, Al2O3, and CaO in terms of oxides. These calcium-containing amorphous aluminosilicates with a Si / Al / Ca molar ratio will undergo a "dissolution, recombination, and condensation" reaction under the action of the alkali activator. The obtained alkali-activated geopolymer material has high strength and good durability, and can be used to prepare blocks or aggregates. However, the cost of this alkali-activated geopolymer concrete is high, which limits its large-scale application in engineering. Summary of the invention
[0004] The present invention aims to solve the technical problem of high cost of existing soft soil solidification methods and provide a preparation and use method of a biogas residue soft soil solidification agent.
[0005] The preparation method of the biogas residue soft soil solidifying agent of the present invention is carried out according to the following steps: 1. Separate the solid and liquid of the biogas residue, and dry the obtained solid phase at a temperature of 95-105°C for 2-3 hours to obtain dry biogas residue; drying the biogas residue facilitates subsequent treatment and also causes the residual microbial colonies to die and inactivate, preventing pathogens from polluting the environment; 2. Add the dry biogas residue into a concentrated sodium hydroxide aqueous solution with a concentration of 3-4 mol / L, soak and stir for 2-3 hours at a temperature of 55-60°C, detect the pH value of the solution every 0.5-1 hour during the soaking and stirring process, and maintain the pH value of the solution at 13-14; then filter, the filtrate is the alkaline leaching solution, and the solid phase is the porous biogas residue; in this step, the silicon dioxide and phosphorus pentoxide in the biogas residue are fully leached by soaking and stirring, and the obtained alkaline leaching solution contains sodium silicate, sodium hydroxide and sodium phosphate. During the soaking process, the continuous consumption of sodium hydroxide will reduce the pH value. The pH value of the solution is tested every 0.5 hours. When the pH value of the solution is lower than 13, sodium hydroxide powder needs to be added to keep the pH value at 13-14. At the same time, the pH value of the solution is maintained at 13-14 to maintain an alkaline environment so that silicon dioxide and phosphorus pentoxide can be fully leached. Stirring is to prevent the formation of colloidal precipitation of sodium silicate. Silicon dioxide and phosphorus pentoxide in the biogas residue hinder the thermal decomposition of organic matter. Concentrated sodium hydroxide is used to leach them. After leaching, a large number of pores appear in the biogas residue, which is conducive to temperature increase and thermal decomposition. Therefore, the biogas residue after soaking is called porous biogas residue. 3. Soak the porous biogas residue in concentrated hydrochloric acid with a concentration of 3-4 mol / L at room temperature for 20-24 hours. During the soaking process, stir it once every 2 hours and detect the pH value, keep the pH value of the solution at 0-1, and then filter it. The filtrate is the acid leaching solution, and the solid phase is the porous deashing biogas residue. In this step, the acid leaching solution contains sodium ions, potassium ions, calcium ions, magnesium ions and aluminum ions. During the soaking process, stir it once every 2 hours and detect the pH value. When the pH value of the solution is higher than 1, it is necessary to add concentrated hydrochloric acid to keep the pH value at 0-1. The alkali metals in the biogas residue exist in the form of compounds, and these alkali metals are called inorganic ash. Some of them are beneficial to pyrolysis, while others are not. After all the alkali metals are removed, a favorable alkali metal catalyst is added, and it can be leached using concentrated hydrochloric acid. The biogas residue after leaching is the deashing biogas residue. 4. After the porous deashing sludge is rinsed until the pH of the washing wastewater is higher than 5, aluminum oxide and / or zinc oxide are added to the porous deashing sludge as a catalyst; after being evenly mixed, it is placed in a high-temperature furnace, heated to 600-650°C at a heating rate of 100-120°C / min in a nitrogen atmosphere, maintained for 10-60inm, and then cooled to room temperature at a cooling rate of 10-15°C / min to obtain porous biochar; the solid product porous biochar obtained in this step has an ultrafine pore structure and strong adsorption effect; the added zinc oxide or aluminum oxide neutralizes the residual hydrochloric acid on the one hand, and acts as a catalyst in the pyrolysis process on the other hand, and water is used to wash away the excess acid to reduce the consumption of aluminum oxide and zinc oxide, thereby reducing costs; 5. The alkaline leaching solution obtained in step 2 is mixed with the acid leaching solution obtained in step 3, and sodium hydroxide powder is added to adjust the pH value to 12-14 to obtain a composite activator; the higher the pH value of the composite activator in this step, the better the hardening effect, and a pH value of 12-13 can meet the basic hardening requirements; 6. According to the mass ratio of granulated blast furnace slag, fly ash beads, activated silica, porous biochar and composite activator of 100: (38-43): (9-12): (1-5): (80-100), the granulated blast furnace slag, fly ash beads, activated silica, porous biochar and composite activator are evenly mixed to obtain a biogas slag soft soil solidifier.
[0006] Furthermore, the amount of zinc oxide or aluminum oxide added in step 4 is calculated as 0.1% to 2% of the mass fraction of the porous deashing biogas slag; the amount of zinc oxide and aluminum oxide added is determined according to the source of the biogas slag, and the biogas slag from different sources has large differences in performance, and the amount of addition is also different; Furthermore, the granulated blast furnace slag described in step six is S95, S105 or S115; blast furnace slag has various numbers such as S95, S105, S115, etc. The larger the number, the higher the activity. The granulated blast furnace slag has higher activity, and the higher the activity, the higher the strength.
[0007] Furthermore, the fly ash beads described in step six are fly ash with a particle size ≥325 mesh after sorting; the fly ash beads have similar chemical properties to fly ash, and fly ash will affect the fluidity of the mixture, but the fly ash beads after sorting can reduce the friction between the mixed particles due to their geometric shape close to spheres, thereby improving the fluidity; at the same time, the particle size of fly ash has a greater influence on activity, but the larger the particle size, the higher the cost, and 325 mesh or above can meet the requirements.
[0008] Furthermore, the mass fraction of silicon dioxide in the active silicon dioxide described in step six is ≥97%, and it is amorphous silicon dioxide with a particle size ≥2000 mesh; active silicon dioxide with a particle size ≥2000 mesh has the ability to improve fluidity.
[0009] The method for using the above-mentioned biogas residue soft soil solidifying agent is carried out according to the following steps: Add the biogas residue soft soil curing agent to the soft soil to be cured, where the mass of the biogas residue soft soil curing agent is 20%~30% of the mass of the soft soil to be cured; add water at the same time, mix evenly, so that the slump of the mixture reaches more than 90mm, and then cure for 21~28 days at a temperature of 20~30℃ and a relative humidity of 85%~90% to complete the curing of the soft soil. The mass of the added water is 0%~30% of the mass of the soft soil to be cured. The additional addition of water is mainly to ensure the fluidity of the cured soil so that it can be fully mixed and evenly added. Adding additional water will reduce the curing strength. For soft soil with high fluidity or high water content, if the fluidity requirements have been met, no additional water is needed. If it is not met, additional water can be added appropriately according to the actual situation. Generally, adding 0~30% of soft soil can meet the fluidity requirements and the strength will not decrease much.
[0010] Biogas residue is a semi-solid substance left at the bottom of the biogas tank after biogas fermentation. It is rich in organic matter, humic acid, crude protein, nitrogen, phosphorus, potassium and trace elements, etc. It contains 30% to 50% organic matter, 10% to 20% humic acid, 0.8% to 2% total nitrogen, 0.4% to 1.2% total phosphorus and 0.6% to 2% total potassium. The biogas residue is first washed with sodium hydroxide aqueous solution and then with concentrated hydrochloric acid to remove the inorganic ash of the biogas residue, so that the pyrolysis efficiency is improved during the pyrolysis process, and the porous biochar obtained becomes looser and more porous, and the specific surface area becomes larger. The composite activator contains sodium ions, potassium ions, calcium ions, magnesium ions and aluminum ions. These alkali metal ions have an enhanced stimulating effect on geopolymer concrete. The calcium ions can enhance the CSH and CASH gels in geopolymer concrete, and the silicate and phosphate ions have the ability to improve the activity of geopolymer cementitious materials. Composite activators are used to activate slag and fly ash, and porous biochar is added to the soil to further fill the pores in the soil, generating geopolymer concrete and improving the soil's ability to resist seawater erosion.
[0011] The present invention realizes the efficient utilization of biogas slag in the field of building materials. A composite activator is obtained by compounding the alkaline and acid washing waste liquids of the biogas slag. The alkalinity of the composite activator itself and the porous filling effect of biochar are utilized. During the curing process, the biochar serves as a crystal nucleus and can act as a carbon skeleton, thereby improving the integrity of the gel material produced by the curing agent and improving the curing effect. At the same time, the wastewater generated in the pyrolysis process itself is utilized as an activator, thereby reducing environmental pollution and lowering treatment costs.
[0012] When the biogas residue soft soil curing agent of the present invention is used, the biogas residue soft soil curing agent can be mixed into the soft soil to be cured and shaped by using a mold, or the biogas residue soft soil curing agent can be directly poured into the soft soil area to be cured, and the added amount of the curing agent is 20% to 30% of the mass of the soft soil. After mixing evenly, a plastic film is covered to prevent water evaporation, and watering is carried out every 4 hours for curing. After 24 hours, the curing is changed to watering every 8 hours. After 3 days, it can have a certain curing strength, and after 28 days, it can reach about 90% of the final strength, which can meet the engineering requirements.
[0013] The soft soil solidified by the biogas residue soft soil solidifying agent of the present invention has an unconfined compressive strength of 2.69-3.28 MPa after 3 days of curing and an unconfined compressive strength of 6.39-7.37 MPa after 28 days of curing, and can be used in the engineering field. DETAILED DESCRIPTION
[0014] The beneficial effects of the present invention are verified by the following examples.
[0015] Example 1: The method of using biogas residue to solidify soft soil in this example is carried out according to the following steps: 1. Separate the solid and liquid of the biogas residue, and dry the obtained solid phase at a temperature of 95-105°C for 2-3 hours to obtain dry biogas residue; drying the biogas residue facilitates subsequent treatment and also causes the residual microbial colonies to die and inactivate, preventing pathogens from polluting the environment; 2. Add the dry biogas residue to a concentrated sodium hydroxide aqueous solution with a concentration of 3 mol / L, soak and stir for 2 hours at a temperature of 60°C, and check the pH value of the solution every 0.5 hours during the soaking and stirring process to maintain the pH value of the solution at 13.5-14. When the pH value of the solution is lower than 13, add sodium hydroxide powder to maintain the pH value at 13.5-14; then filter, the filtrate is an alkaline leaching solution, and the solid phase is porous biogas residue; in this step, the continuous consumption of sodium hydroxide during the soaking process will reduce the pH value, and it is necessary to replenish sodium hydroxide powder in time to maintain the pH value of the solution at 13-14, so that the silicon dioxide and phosphorus pentoxide in the biogas residue can be fully leached, and the obtained alkaline leaching solution contains sodium silicate, sodium hydroxide, and sodium phosphate. Stirring is to prevent sodium silicate from forming colloidal precipitation; silicon dioxide and phosphorus pentoxide compounds in the biogas residue hinder the pyrolysis of organic matter, and concentrated sodium hydroxide is used to leach them. After leaching, a large number of pores appear in the biogas residue, which is conducive to heating and pyrolysis. Therefore, the biogas residue after soaking is called porous biogas residue; 3. Soak the porous biogas residue in 3 mol / L concentrated hydrochloric acid at room temperature for 24 hours. Stir once every 2 hours during the soaking process and detect the pH value, keep the pH value of the solution at 0-1, and then filter. The filtrate is the acid leaching solution, and the solid phase is the porous deashed biogas residue. In this step, the acid leaching solution contains sodium ions, potassium ions, calcium ions, magnesium ions and aluminum ions. The alkali metals in the biogas residue exist in the form of compounds, and these alkali metals are called inorganic ash. Some of them are beneficial to pyrolysis, while others are not. After all the alkali metals are removed, a beneficial alkali metal catalyst is added, and it can be leached using concentrated hydrochloric acid. The biogas residue after leaching is the deashed biogas residue. 4. After the porous deashing sludge is rinsed until the pH of the washing wastewater is higher than 5, 10 grams of aluminum oxide and 10 grams of zinc oxide are added to 1000 grams of porous deashing sludge as catalysts; after being evenly mixed, it is placed in a high-temperature furnace, heated to 600°C at a heating rate of 120°C / min in a nitrogen atmosphere and maintained for 60inm, and then cooled to room temperature at a cooling rate of 10°C / min, and the solid phase is ground to a particle size of less than 80um to obtain porous biochar, while producing by-products of methane and kerosene; the solid product porous biochar obtained in this step has an ultrafine pore structure and strong adsorption effect; the added zinc oxide and aluminum oxide neutralize the residual hydrochloric acid on the one hand, and act as catalysts in the pyrolysis process on the other hand, and water is used to wash away the excess acid to reduce the consumption of aluminum oxide and zinc oxide, thereby reducing costs; 5. The alkaline leaching solution obtained in step 2 and the acid leaching solution obtained in step 3 are mixed in a volume ratio of 1:1, and sodium hydroxide powder is added to adjust the pH value to 14 to obtain a composite activator; 6. Mix 100 grams of granulated blast furnace slag S95, 40 grams of fly ash beads with a particle size of 325 mesh, 10 grams of activated silica with a particle size of 2000 mesh, 5 grams of porous biochar prepared in step 4, and 100 grams of the composite activator prepared in step 5, wherein the mass fraction of silica in the active silica is 98%, and obtain a sludge soft soil solidifier.
[0016] The porous biochar obtained in step 4 of this embodiment has a huge specific surface area and good pore distribution. The specific surface area is 405 m2 / g, and the pore size is mainly distributed between 4 and 40 nm.
[0017] Comparative Example 1: This comparative example differs from Example 1 in that "100 grams of composite stimulant" in step six is replaced by "90 grams of composite stimulant", and the other steps and parameters are the same as those in Example 1.
[0018] Comparative Example 2: This comparative example differs from Example 1 in that "100 grams of composite stimulant" in step six is replaced by "80 grams of composite stimulant", and the other steps and parameters are the same as those in Example 1.
[0019] The soft soil of a subway line in Nansha District, Guangzhou was used as the soft soil to be solidified. The moisture content of the soft soil to be solidified was 40.6%. The soft soil solidifying agents prepared in Example 1, Comparative Examples 1 and 2 were used for solidification respectively. The specific steps were as follows: 185 grams of biogas residue soft soil curing agent was added to 616 grams of soft soil to be cured and mixed evenly. The slump of the mixture was 100 mm. The mixture was placed in a mold, and after coating, it was placed in a standard curing room with a temperature of 20°C and a relative humidity of 90% for 24 hours before demoulding. Then, the green body was cured for 28 days under the conditions of a temperature of 20 degrees Celsius and a relative humidity of 90%. The unconfined compressive strength was tested at 3 days and 28 days of curing. At the same time, 185 grams of cement was added as a curing agent to 616 grams of soft soil to be cured for reference, and the results are shown in Table 1.
[0020] Table 1 Strength results of Example 1, Comparative Examples 1, 2 and cement-cured soil after 3 days and 28 days of curing
[0021] Compared with the same amount of cement added, the biogas residue soft soil curing agent prepared in Example 1 has a 3-day strength increase of 29.64% and a 28-day strength increase of 18.87%. It can also be seen from Table 1 that increasing the amount of composite activator has a significant improvement in the curing effect of the soft soil curing agent. This is because the composite activator contains sodium, potassium, calcium, magnesium, aluminum, silicate, phosphoric acid and other ions that can stimulate the activity of the curing agent substrate (granulated blast furnace slag, fly ash beads, active silica), promote its hydration to generate CSH gel and CASH gel, thereby improving the curing strength, especially the early strength improvement.
[0022] Comparative Example 3: This comparative example differs from Example 1 in that the “5 grams of porous biochar” in step six is replaced by “3 grams of porous biochar”, and the other steps and parameters are the same as those in Example 1.
[0023] Comparative Example 4: This comparative example differs from Example 1 in that "5 grams of porous biochar" in step six is replaced by "1 gram of porous biochar", and the other steps and parameters are the same as those in Example 1.
[0024] The soft soil of a subway line in Nansha District, Guangzhou is used as the soft soil to be solidified. The moisture content of the soft soil to be solidified is 40.6%. The soft soil solidifying agents prepared in Comparative Examples 3 and 4 are used for solidification. The specific steps are: 185 grams of the soft soil solidifying agent is added to 616 grams of the soft soil to be solidified and mixed evenly. The slump of the mixture is 100 mm. The mixture is put into a mold, and after laminating, it is placed in a standard curing room with a temperature of 20°C and a relative humidity of 90%, and then demolded after 24 hours. Then, the green body is placed at a temperature of 20 degrees Celsius and a relative humidity of 90% for 28 days. The unconfined compressive strength is tested at 3 days and 28 days of curing. The results are shown in Table 2.
[0025] Table 2 Strength results of the cured soil of Comparative Examples 3 and 4 after 3 and 28 days of curing
[0026] The 3-day strength of the solidified soil of the biogas residue soft soil solidifying agent prepared in comparative example 3 is 3.05% lower than that of Example 1, and the 28-day strength is 3.93% lower than that of Example 1; the 3-day strength of the solidified soil of the biogas residue soft soil solidifying agent prepared in comparative example 4 is 17.38% lower than that of Example 1, and the 28-day strength is 7.06% lower than that of Example 1. This indicates that increasing the amount of porous biochar has a significant improvement in the solidification effect of the soft soil solidifying agent, because the porous biochar has a filling, adsorption, and nucleation effect on the pores in the soil, which improves the solidification strength.
[0027] The soft soil of a subway line in Nansha District, Guangzhou City was used as the soft soil to be solidified, and the moisture content of the soft soil to be solidified was 40.6%. The soft soil was solidified using the biogas slag soft soil curing agent of Example 1. The specific steps were as follows: two portions of 185 grams of biogas slag soft soil curing agent were weighed, one portion was added to 925 grams of the soft soil to be solidified and mixed evenly (the amount of the biogas slag soft soil curing agent added was 20%), and the other portion was added to 1850 grams of the soft soil to be solidified and mixed evenly (the amount of the biogas slag soft soil curing agent added was 10%). The slump of the mixture was 100 mm and 100 mm, respectively. The mixture was loaded into a mold, and after coating, it was placed in a standard curing room at a temperature of 20°C and a relative humidity of 90%, and then demolded after 24 hours. Then the green body was cured at a temperature of 20 degrees Celsius and a relative humidity of 90% for 28 days, and the unconfined compressive strength was tested at 3 days and 28 days of curing, respectively. The strength of the stabilized soil was tested under different addition amounts of biogas residue soft soil stabilizer, and the results are shown in Table 3.
[0028] Table 3 3-day and 28-day strength results of the biogas residue soft soil solidifier of Example 1 under different incorporation conditions
[0029] As can be seen from Table 3, the amount of soft soil curing agent added has a great influence on the curing effect of soft soil. Under the condition of 20% addition, the 3-day strength of the cured soil is 17.99% lower than that of the cured soil with 30% addition in Example 1, and the 28-day strength is 13.30% lower; under the condition of 10% addition, the 3-day strength of the cured soil is 51.52% lower than that of the cured soil with 30% addition in Example 1, and the 28-day strength is 38.26% lower. It shows that reducing the amount of soft soil curing agent added will reduce the curing effect of soft soil. The main reason is that the gel material produced by the curing agent is reduced, which reduces the strength of the cured soil. In application, the most economical and appropriate amount is selected according to engineering requirements.
[0030] Comparative Example 5: This comparative example is different from Example 1 in that the biogas residue is not subjected to alkaline leaching. The specific method is carried out according to the following steps: 1. Separating the biogas residue into solid and liquid, and drying the obtained solid phase at 100°C for 2 hours to obtain dry biogas residue; 2. Soak the dry biogas residue in 3 mol / L concentrated hydrochloric acid at room temperature for 24 hours, keep the pH value of the solution at 0 during the soaking process, and then filter. The filtrate is the acid leaching solution, and the solid phase is the porous deashing biogas residue; 3. Add 10 g of zinc oxide and 10 g of aluminum oxide to 1000 g of porous deashing sludge and mix them evenly. Then heat the mixture to 600 ° C at a rate of 120 ° C / min in a nitrogen atmosphere and keep it for 1 hour for pyrolysis. After the pyrolysis is completed, cool it at a cooling rate of 10 ° C / min, grind the obtained solid phase to a particle size of less than 80 um, and obtain porous biochar; at the same time, produce by-products such as methane and kerosene; 4. Add sodium hydroxide powder to the acid leaching solution obtained in step 2 to adjust the pH to 14 as an activator; 5. Mix 100 grams of granulated blast furnace slag S95, 40 grams of fly ash beads with a particle size of 325 mesh, 10 grams of activated silica with a particle size of 2000 mesh, 5 grams of porous biochar prepared in step three, and 100 grams of the activator prepared in step four, wherein the mass fraction of silica in the active silica is 98%, and obtain a biogas slag soft soil solidifier.
[0031] The sludge soft soil curing agent prepared in Comparative Example 5 was added to 616 grams of soft soil of the same type as that in Example 1 to be cured in sequence and mixed evenly. After molding, the film was covered and placed in the laboratory. The molds were demolded after 24 hours and cured for 3 days and 28 days at a temperature of 20 degrees Celsius and a relative humidity of 90%. The 3-day strength was measured to be 2.68 MPa (18.29% lower than that in Example 1), and the 28-day strength was 5.67 MPa (23.07% lower than that in Example 1).
[0032] The soft soil of a subway line in Nansha District, Guangzhou was used as the soft soil to be solidified, and the moisture content of the soft soil to be solidified was 40.6%. The soft soil solidifying agent of the sludge in comparative example 5 was used for solidification. The specific steps were as follows: the sludge soft soil solidifying agent prepared in comparative example 5 was added to 616 grams of the soft soil to be solidified and mixed evenly. The slump of the mixture was 100 mm. The mixture was put into a mold, and after coating, it was placed in a standard curing room with a temperature of 20°C and a relative humidity of 90%, and then demolded after 24 hours. Then, the green body was placed at a temperature of 20 degrees Celsius and a relative humidity of 90% for 28 days, and the unconfined compressive strength was tested at 3 days and 28 days of curing. The 3-day strength was measured to be 2.68 MPa, which was 18.29% lower than that of Example 1, and the 28-day strength was 5.67 MPa, which was 23.07% lower than that of Example 1. In this comparative example, the specific surface area of the porous biochar obtained without alkaline leaching of the biogas residue is 265m2 / g, and the pore size is mainly distributed between 80 and 200nm. The specific surface area of the porous biochar obtained without alkaline leaching is small, and the pore size distribution is not as good as that of Example 1. This is mainly because the silicon dioxide and phosphorus pentoxide compounds in the biogas residue fill the porous biochar, reducing its specific surface area.
[0033] Comparative Example 6: This comparative example is different from Example 1 in that the biogas residue is not subjected to acid leaching. The specific method is carried out according to the following steps: 1. Separating the biogas residue into solid and liquid, and drying the obtained solid phase at 100°C for 2 hours to obtain dry biogas residue; 2. Add the dry biogas residue into a concentrated sodium hydroxide aqueous solution with a concentration of 3 mol / L, soak and stir at a temperature of 60°C for 2 hours, keep the pH value of the solution at 14 during the soaking and stirring process, and then filter. The filtrate is the alkaline leaching solution, and the solid phase is the porous biogas residue; 3. Add 10 grams of zinc oxide and 10 grams of aluminum oxide to 1000 grams of porous biogas residue and mix them evenly. Then heat the mixture to 600°C at a rate of 120°C / min in a nitrogen atmosphere and keep it for 1 hour for pyrolysis. After the pyrolysis is completed, cool it at a cooling rate of 10°C / min, grind the obtained solid phase to a particle size of less than 80um, and obtain porous biochar; at the same time, produce by-products such as methane and kerosene; 4. Add sodium hydroxide powder to the alkaline leaching solution obtained in step 2 to adjust its pH value to 14 as an activator; 5. Mix 100 grams of granulated blast furnace slag S95, 40 grams of fly ash beads with a particle size of 325 mesh, 10 grams of activated silica with a particle size of 2000 mesh, 5 grams of porous biochar prepared in step three, and 100 grams of the activator prepared in step four, wherein the mass fraction of silica in the active silica is 98%, and obtain a biogas slag soft soil solidifier.
[0034] The soft soil of a subway line in Nansha District, Guangzhou was used as the soft soil to be solidified, and the moisture content of the soft soil to be solidified was 40.6%. The soft soil solidifying agent of the sludge in comparative example 5 was used for solidification. The specific steps were as follows: the sludge soft soil solidifying agent prepared in comparative example 6 was added to 616 grams of the soft soil to be solidified and mixed evenly. The slump of the mixture was 100 mm. The mixture was put into a mold, and after coating, it was placed in a standard curing room with a temperature of 20°C and a relative humidity of 90% and then demolded after 24 hours. Then, the green body was placed at a temperature of 20 degrees Celsius and a relative humidity of 90% for 28 days, and the unconfined compressive strength was tested at 3 days and 28 days of curing. The 3-day strength was measured to be 2.76 MPa, which was 15.85% lower than that of Example 1, and the 28-day strength was 7.01 MPa, which was 4.88% lower than that of Example 1. The specific surface area of the porous biochar obtained without alkaline leaching of the biogas residue in this comparative example is 385 m2 / g, and the pore size is mainly distributed between 20 and 100 nm. The specific surface area and pore size distribution of the porous biochar obtained without acid leaching are not as good as those in Example 1, but better than those obtained without alkaline leaching in Comparative Example 5. This is mainly because the alkaline leaching causes the silicon dioxide and phosphorus pentoxide compounds in the biogas residue to be leached out, making the biogas residue loose, and some alkali metals inhibit the pyrolysis production, resulting in insufficient pyrolysis, and the formed pores are slightly worse than those in Example 1.
Claims
1. A method for preparing a biogas residue soft soil solidifying agent, characterized in that: The method proceeds as follows:
1. Separate the biogas residue into solid and liquid, and dry the obtained solid phase at a temperature of 95-105°C for 2-3 hours to obtain dry biogas residue; 2. Add the dry biogas residue to a concentrated sodium hydroxide aqueous solution with a concentration of 3-4 mol / L, soak and stir for 2-3 hours at a temperature of 55-60°C, and test the pH value of the solution every 0.5-1 hour during the soaking and stirring process to maintain the pH value of the solution at 13-14; then filter, the filtrate is the alkaline leaching solution, and the solid phase is the porous biogas residue; 3. Soak the porous biogas residue in concentrated hydrochloric acid with a concentration of 3-4 mol / L at room temperature for 20-24 hours. Stir and test the pH value every 2 hours during the soaking process to keep the pH value of the solution at 0-1. Then filter it. The filtrate is the acid leaching solution and the solid phase is the porous deashing biogas residue.
4. After the porous deashing sludge is rinsed until the pH of the washing wastewater is higher than 5, aluminum oxide and / or zinc oxide are added to the porous deashing sludge as a catalyst; after being evenly mixed, it is placed in a high-temperature furnace, heated to 600-650°C at a heating rate of 100-120°C / min in a nitrogen atmosphere, and maintained for 10-60inm, and then cooled to room temperature at a cooling rate of 10-15°C / min to obtain porous biochar; 5. The alkaline leaching solution obtained in step 2 is mixed with the acid leaching solution obtained in step 3, and sodium hydroxide powder is added to adjust the pH value to 12-14 to obtain a composite activator; 6. According to the mass ratio of granulated blast furnace slag, fly ash beads, activated silica, porous biochar and composite activator of 100: (38-43): (9-12): (1-5): (80-100), the granulated blast furnace slag, fly ash beads, activated silica, porous biochar and composite activator are evenly mixed to obtain a biogas slag soft soil solidifier.
2. The method for preparing a biogas residue soft soil solidifying agent according to claim 1, characterized in that: The amount of zinc oxide or aluminum oxide added in step 4 is calculated as 0.1% to 2% of the mass fraction of the porous deashing sludge.
3. The method for preparing a biogas residue soft soil solidifying agent according to claim 1 or 2, characterized in that: The granulated blast furnace slag described in step six is S95, S105 or S115.
4. The method for preparing a biogas residue soft soil solidifying agent according to claim 1 or 2, characterized in that: The fly ash beads described in step six are fly ash with a particle size of ≥325 mesh after sorting.
5. The method for preparing a biogas residue soft soil solidifying agent according to claim 1 or 2, characterized in that: The mass fraction of silicon dioxide in the active silicon dioxide described in step six is ≥97%, and it is amorphous silicon dioxide with a particle size of ≥2000 mesh.
6. A method for using the biogas residue soft soil solidifying agent prepared by the method of claim 1, characterized in that: The method is carried out according to the following steps: adding a biogas residue soft soil curing agent to the soft soil to be cured, wherein the mass of the biogas residue soft soil curing agent is 20% to 30% of the mass of the soft soil to be cured; adding water at the same time, mixing evenly, so that the slump of the mixture reaches more than 90 mm, and then curing for 21 to 28 days at a temperature of 20 to 30°C and a relative humidity of 85% to 90% to complete the curing of the soft soil.
Citation Information
Patent Citations
Alkali-activated geopolymer materials and their applications
CN115974431B